"I follow what you post!": The role of social media influencers' content characteristics in consumers' online brand-related activities (COBRAs). (May 2022) - Cheung, Man Lai; Leung, Wilson K.S.; Aw, Eugene Cheng-Xi; Koay, Kian Yeik
Abstract: The purpose of this research is to examine the underlying mechanisms through which social media influencers' (SMI) content characteristics (information, design, and technology quality and creativity) influence consumers' online brand-related activities (COBRAs) (consume, contribute, and create) through parasocial relationships and wishful identification. Grounded in the integration of the two-step flow theory, social influence theory, and power theory, a conceptual model is proposed and empirically tested using a sample of 263 social media users who had followed at least one social media influencer on social media. We analyzed the data using partial least squares structural equation modeling (PLS-SEM) and necessary condition analysis (NCA). The results reveal that three of the four dimensions of SMI's content characteristics, namely design quality, technology quality, and creativity are significant predictors of parasocial relationships. Design quality and creativity are significant predictors of wishful identification. Parasocial relationships and wishful identification are also identified as significant predictors of COBRAs. The results of NCA analysis also identify the proposed content characteristics as necessary factors required to foster COBRAs. This study offers valuable insights into how social media influencers can position themselves to be more effective in promoting brands and products through the curation of their social media content.